The influence of sex chromosome aneuploidy on brain asymmetry. - Rezaie, R; Daly, E; Cutter, W; Murphy, D; Robertson, D; DeLisi, L; Mackay, C; Barrick, T; Crow, T; Roberts, N (2009)
The cognitive deficits present in individuals with sex chromosome aneuploidies suggest that hemispheric differentiation of function is determined by an X-Y homologous gene [Crow (1993); Lancet 342:594-598]. In particular, females with Turner's syndrome (TS) who have only one X-chromosome exhibit deficits of spatial ability whereas males with Klinefelter's syndrome (KS) who possess a supernumerary X-chromosome are delayed in acquiring words. Since spatial and verbal abilities are generally associated with right and left hemispheric function, such deficits may relate to anomalies of cerebral asymmetry. We therefore applied a novel image analysis technique to investigate the relationship between sex chromosome dosage and structural brain asymmetry. Specifically, we tested Crow's prediction that the magnitude of the brain torque (i.e., a combination of rightward frontal and leftward occipital asymmetry) would, as a function of sex chromosome dosage, be respectively decreased in TS women and increased in KS men, relative to genotypically normal controls. We found that brain torque was not significantly different in TS women and KS men, in comparison to controls. However, TS women exhibited significantly increased leftward brain asymmetry, restricted to the posterior of the brain and focused on the superior temporal and parietal-occipital association cortex, while KS men showed a trend for decreased brain asymmetry throughout the frontal lobes. The findings suggest that the number of sex chromosomes influences the development of brain asymmetry not simply to modify the torque but in a complex pattern along the antero-posterior axis.